Ultramicroscopic features of thyrocytes after 60 days of tartrazine administration and infliction of a defect in the tibiaе and substantiation of the effectiveness of sodium selenite - V. N. Morozov; V. I. Luzin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Aim. Identify the features of the ultramicroscopic structure of thyrocytes in rats under conditions after 60 days of tartrazine administration and simulated traumatic bone defect, as well as to establish the effectiveness of sodium selenite.Material and methods. White mature male rats were divided into 3 groups. In Group 1, a through defect in the tibiae was applied to rats after the previous 60-day intragastric administration of saline solution. In Group 2, rats were subjected to 60-day exposure with tartrazine at a dosage of 750 mg/kg instead of saline solution under similar experimental conditions and in Group 3 – additionally intramuscularly injected sodium selenite at a dose of 40 µg/kg. On days 3, 10, 15, 24 and 45, the animals were removed from the experiment, samples of thyroid gland were processed for electron microscopic examination according to the standard method.Results. In Group 2, inactive chromatin prevailed in the nucleus, expanded cisterns of the rough endoplasmic reticulum, single mitochondria with matrix destruction sites were observed in the cytoplasm from 3rd to 15th days of experiment. There were cells in a state of apoptosis. By the day 24, the ultramicroscopic picture was almost restored to the control values.In Group 3, an increase in the area of active euchromatin in the nucleus, restoration of the lumen of the cisterns of the rough endoplasmic reticulum, an increase in the number of lysosomes in the cytoplasm, a decrease in the number of mitochondria with signs of destruction of crysts and cells with signs of apoptosis were revealed.Conclusion. The bone defect applied after the previous 60-day administration of tartrazine causes an aggravation of ultramicroscopic changes in thyrocytes, compared with the group without the introduction of a food additive. Use of sodium selenite allows, to a certain extent, to neutralize the changes caused by tartrazine in these cells by the time of traumatic injury.